2017
DOI: 10.1136/bmj.i6770
|View full text |Cite
|
Sign up to set email alerts
|

Financial ties of principal investigators and randomized controlled trial outcomes: cross sectional study

Abstract: Objective To examine the association between the presence of individual principal investigators’ financial ties to the manufacturer of the study drug and the trial’s outcomes after accounting for source of research funding.Design Cross sectional study of randomized controlled trials (RCTs).Setting Studies published in “core clinical” journals, as identified by Medline, between 1 January 2013 and 31 December 2013.Participants Random sample of RCTs focused on drug efficacy.Main outcome measure Association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
115
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(119 citation statements)
references
References 47 publications
2
115
0
2
Order By: Relevance
“…14 Recently, Ahn and colleagues 15 reported that a principal investigator's personal financial ties to drug makers are linked to positive study conclusions.…”
mentioning
confidence: 99%
“…14 Recently, Ahn and colleagues 15 reported that a principal investigator's personal financial ties to drug makers are linked to positive study conclusions.…”
mentioning
confidence: 99%
“…Financial ties of principal investigators seem to be independently associated with positive clinical trial results [13]. In addition, financial conflicts of interest may bias the dissemination of study findings, such as the display of strong advocacy by investigators on social media.…”
mentioning
confidence: 99%
“…This association holds for both direct sponsorship4 and more indirectly through the financial links of principal investigators leading clinical trials and the outcomes of those trials 5. Doctors who receive even inexpensive meals from drug companies are more likely to prescribe their brands, with a dose response seen by the numbers and price of meals received within four drug classes 6…”
mentioning
confidence: 99%